Advanced Landscapes: A Structured Pedagogy of Process. (2nd January 2020) - Wall, Ed
Abstract: Guest‐Editor Ed Wall charts the history and successes of the Advanced Landscape and Urbanism group at the University of Greenwich where he is Academic Portfolio Lead, and illustrates the exploratory nature of its pedagogy.